Rio de Janeiro: uma análise da perda recente de centralidade - Ana Claudia Nonato da Silva Loureiro (2006)
This work analyses the explanatory factors of the recent Rio de Janeiro`s lost of centrality. The analysis starts at the 1970´s, when the transference of the public machine to Brasilia accelerates, at the same time that São Paulo stands out like the largest national metropolis, reinforcing his control position on national economy, and the strengthening of second level urban centers contributes to the relative de-concentration of national production and wealth. The lost of Rio de Janeiro`s traditional central functions and the lack of an integrated and complementary area where analyzed on the context of the urban dynamics on contemporary capitalism.